Natural School Management: A New Paradigm for Education - Firman Firman; Friscilla Wulan Tersta; Eva Iryani (Universitas Negeri Padang, 2021)
School of nature is one of the new concepts in the world of education. The natural school is basically an alternative form of education that uses the universe as a place of learning, teaching material and also as an object of learning. According to some experts, it is believed that this concept is an effective approach for the realization of activities related to active learning. The aims of this research are to investigate how the management of natural schools works, specifically in planning, organizing, actuating, and controlling. This study utilized qualitative method with a case study approach. The data were collected by semi structure interview, observation and documentation. The data were then analyzed, described, and interpreted comprehensively. The data revealed that character education and religion are emphasized to the students in teaching and learning process. There are 3 curriculum adopted in the management of this natural school, namely: Curriculum implemented by the national Education Office, IT (Islam terpadu) curriculum, and BBA curriculum (learning with nature). It was agreed to create an academic student and balanced character.